Rancang Bangun Sistem Penjadwalan Wawancara Mahasiswa Baru STMIK STIKOM Indonesia (LP2M INSTITUT TEKNOLOGI DAN BISNIS ASIA MALANG, 2017)
Scheduling interview system for prospective students in STMIK STIKOM Indonesia is currently carried out by manually recording it in a ledger. Some constraints faced are: the schedule made by Front Office as the admission is not in accordance to the Counselor’s schedule and schedule clashes often occur between one student and another, so that students often have to queue for long time to do the counseling. This will cause disappointment for the students and they will consider that the Campus give bad service for the students. This research will be started with observing the existing system, then perform the Requirement Analysis from the system’s user, and then do the development process. The Scheduling process in this system using First In First Out method. The final phase of this research is to do the testing using Blackbox method. This Prospective Students Interview Scheduling was built in order to have better arrangement for the interview schedule of all Prospective Students in STMIK STIKOM Indonesia, so as to improve the quality of service to new students. The system begins with the students data entry by the Counselor, then proceed with scheduling and email sending process to the students directly. When the schedule has been submitted, the Prospective Students will conduct the interview according to the schedule that has been arranged, and the Counselor can record the interview’s results in the system. It is expected that STMIK STIKOM Indonesia can improve the quality of service for the Prospective Students.